2014
DOI: 10.12891/ceog16012014
|View full text |Cite
|
Sign up to set email alerts
|

The sympathetic neural hyperalgesia/edema syndrome, a common cause of female pelvic pain, manifesting as a pseudopheochromocytoma with marked clinical improvement with sympathomimetic amines

Abstract: To show that a common but not well-known disorder of the sympathetic nervous system can present with symptoms suggesting a pheochromocytoma. Materials and Methods: The standard treatment of this disorder (which is characterized by an abnormal water load test), i.e., sympathomimetic amine therapy, was given to a woman with paroxysmal tachycardia and hypertension. Results: Over a period of six months, the treatment eradicated the paroxysmal symptoms to which all other therapies had failed. Conclusions: This cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Transdermal buprenorphine was shown to alleviate intractable abdominal pain in 4 children with PIPO (268). Dextroamphetamine sulfate in combination with L‐thyroxin decreased abdominal pain in a 23‐year‐old patient with CIPO (269).…”
Section: 3 Drugs/pharmacotherapymentioning
confidence: 99%
“…Transdermal buprenorphine was shown to alleviate intractable abdominal pain in 4 children with PIPO (268). Dextroamphetamine sulfate in combination with L‐thyroxin decreased abdominal pain in a 23‐year‐old patient with CIPO (269).…”
Section: 3 Drugs/pharmacotherapymentioning
confidence: 99%
“…The name sympathetic neural hyperalgesia edema syndrome seems to be related to certain tissues being more susceptible to permeability by toxic chemicals, coupled with hypofunction of the sympathetic nervous system (which is the main neurologic control of cellular permeability). This is the basis of many autoimmune disorders or allergic reactions leading to hives, rheumatoid arthritis, or other "autoimmune disorders [1][2][3][9][10][11]. One young women "dying" from autoimmune hepatitis immediately responded to dextroamphetamine sulfate and is now perfectly normal [12].…”
Section: Discussionmentioning
confidence: 99%
“…A recent editorial suggested that dextroamphetamine sulfate may be the single most effective treatment for a large variety of disorders especially prevalent in women [1]. Probably the most common use for the amphetamine by the gynecologist is pelvic pain, but the editorial mentioned a large variety of conditions both specific to women, more common to women, or also present in men [1][2][3][4]. It is known as the sympathetic neural hyperalgesia edema syndrome [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports of dopaminergic effi cacy for insidious headaches [57,58]. Other times there may be a suspected etiology e.g., keratoconus, intra-cranial hypertension (pseudotumor cerebri) temporomandibular joint syndrome, or concussions [59][60][61][62]. In the case report on headaches following a concussion not only did the 2 teenagers get immediate relief from severe constant headaches and mental confusion despite months of no relief, but also immediately corrected severe post-traumatic stuttering [62].…”
Section: Dopaminergic Drugs To Treat Medical Conditions That Are More...mentioning
confidence: 97%
“…with their dopaminergic activity provided dramatic relief for 2 women with gastroparesis. One of the women seemed to over metabolize the amphetamine so that 150 mg amphetamine salts were needed to cause complete remission of the disorder which previously over 10 years caused her to be hospitalized 8-10 times per year with at least 1 week stays [74,75]. Interestingly a man with the problem also improved but had marked side eff ects of tachycardia and hypertension with standard dosages.…”
Section: Amphetaminesmentioning
confidence: 99%